Onset and Evolution of Southern Annular Mode-Like Changes at Centennial Timescale - Moreno, P. I.; Vilanova, I.; Villa Martinez, Rodrigo Patricio; Dunbar, R. B.; Mucciarone, D. A.; Kaplan, M. R.; Garreaud, R. D.; Rojas, M.; Moy, C. M.; De Pol Holz, Ricardo Hernán; Lambert, F. (My University, 2018)
The Southern Westerly Winds (SWW) are the surface expression of geostrophic winds that encircle the southern mid-latitudes. In conjunction with the Southern Ocean, they establish a coupled system that not only controls climate in the southern third of the world, but is also closely connected to the position of the Intertropical Convergence Zone and CO2 degassing from the deep ocean. Paradoxically, little is known about their behavior since the last ice age and relationships with mid-latitude glacier history and tropical climate variability. Here we present a lake sediment record from Chilean Patagonia (51 degrees S) that reveals fluctuations of the low-level SWW at mid-latitudes, including strong westerlies during the Antarctic Cold Reversal, anomalously low intensity during the early Holocene, which was unfavorable for glacier growth, and strong SWW since similar to 7.5 ka. We detect nine positive Southern Annular Mode-like events at centennial timescale since similar to 5.8 ka that alternate with cold/wet intervals favorable for glacier expansions (Neoglaciations) in southern Patagonia. The correspondence of key features of mid-latitude atmospheric circulation with shifts in tropical climate since similar to 10 ka suggests that coherent climatic shifts in these regions have driven climate change in vast sectors of the Southern Hemisphere at centennial and millennial timescales.
Keywords: Centennial; Mode (computer interface)